Industrial Conﬂ icts in Modern Russia - Ирина Марковна Козина (Journal of Economic Sociology, 2010)
The paper is devoted to particularities of strike movements in Russia in the 1990s and 2000s. The strike movement dynamics and its relation to the Russian economy’s functioning are studied through the changes in social and labor sphere and regulatory practices. Based on case-studies of recent strikes, the paper focuses on how trade-unions organize and institutionalize labor conﬂ icts and views what factors drive industrial conﬂ icts in the new economic era.